Ferroportin-related haemochromatosis associated with novel Y64H mutation of the SCL40A1 gene - Raszeja-Wyszomirska, Joanna; Caleffi, Angela; Milkiewicz, Piotr; Pietrangelo, Antonello (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
In this paper we described the first Polish patient with ferroportin disease. Hereditary haemochromatosis (HH) is a condition associated with universal iron overload, and it is divided into four types, according to the Online Mendelian Inheritance in Man (OMIM) database. Ferroportin disease represented a rare type of HH, with autosomal dominant trait of inheritance. In our patient we detected a novel mutation in the ferroportin gene, with non-classical phenotype.